Proposal of an instrument to evaluate youths’ knowledge on contraceptive methods - Silva, Nancy Capretz Batista da; Bomfim, Thiago; Cardozo, Nilceu Pfitter; Franco, Maria Aparecida Paiva; Marques, Susi Lippi (Paidéia (Ribeirão Preto), 2007)
In Brazil, the occurrence of pregnancy in adolescence has generated discussions and concern in the public health area. Considering that the association with inadequate use of contraceptive methods is direct, it is essential to evaluate adolescents' knowledge regarding these methods to intervene appropriately. This study aimed to evaluate the efficacy of a questionnaire built to measure the knowledge of high schools students in a city in the interior of Sao Paulo. Lack of adequate knowledge about contraceptive methods (how they are, use, efficacy, indication) was found, despite gender and type of school. The instrument presented satisfactory psychometric levels, reliability and appropriateness to be used as evaluation tool. Its use can support the elaboration of interventions towards improved knowledge on contraceptive methods, safe sex, and reduced rates of pregnancy in adolescence.